Clozapine and incidence of myocarditis and sudden death – Long term Australian experience. (1st July 2017) - Khan, Arshad A.; Ashraf, Asma; Baker, David; Al-Omary, Mohammed S.; Savage, Lindsay; Ekmejian, Avedis; Singh, Rajinder Singh Harjit; Brienesse, Stephen; Majeed, Tazeen; Gordon, Tracy; Drinkwater, Vincent; Collins, Nicholas J.
Abstract: Background: Clozapine is the cornerstone of therapy for refractory schizophrenia; however, the potential for cardiotoxicity is an important limitation in its use. In the current analysis we sought to evaluate the long term cardiac outcomes of clozapine therapy. Methods: All-cause mortality, incidence of sudden death and time to myocarditis were assessed in a cohort of patients maintained on clozapine between January 2009 and December 2015. All patients had regular electrocardiograms, complete blood count, clozapine levels and echocardiography as part of a formal protocol. Results: A total of 503 patients with treatment-resistant schizophrenia were maintained on clozapine during the study period of which 93 patients (18%) discontinued therapy with 29 (6%) deaths. The incidence of sudden death and myocarditis were 2% (n = 10) and 3% (n = 14) respectively. Amongst patients with sudden death, 7 out of 10 (70%) were documented to have used illicit drugs prior to death, with a tendency to weight gain also noted. The mean time to myocarditis post clozapine commencement was 15 ± 7 days. The reduction in left ventricular ejection fraction in those with myocarditis was 11 ± 2%. Conclusion: Myocarditis and sudden cardiac death are uncommon but clinically important complications in a cohort of patients followed while maintained on clozapine undergoing regular cardiac assessment. Further studies are required to document the role of preventive measures for left ventricular dysfunction and sudden cardiac death in this population.